The German Minimum Wage: Effects on Productivity, Profitability, and Investments - Bossler, Mario; Gürtzgen, Nicole; Lochner, Benjamin; Betzl, Ute; Feist, Lisa (Jahrbücher für Nationalökonomie und Statistik, 2019)
In this article, we analyze the effects of the introduction of the German minimum wage using difference-in-differences estimations applied to the IAB Establishment Panel. The treatment effects on the treated establishments show a significant increase in personnel costs. When we analyze the effects of the minimum wage on the net sales of intermediates, we observe a reduction, which is fully explained by the increase in wage costs induced by the minimum wage. The results do not point to effects on establishment-level productivity or capital investments. Looking at investments in human capital, we do not observe any effects on apprenticeship offers or the placement of apprentices. If anything, the results point at a slight reduction in the provision of further training.
CRIS-Team Scopus Importer:2019-08-13
Keywords: minimum wage; productivity; profitability; training